Kecenderungan Anak Bermain Gawai Hubungannya Dengan Motivasi Dan Prestasi Belajar - Ahmad Hanafi (EduBase : Journal of Basic Education, 2020)
Not a few children today, who call themselves millennial generation, compile in support of your goals, son? They answered that they no longer wanted to be doctors, engineers or others. AS want to be a YouTuber or a gamer. The results of this study indicate a link between the tendency of children to play Gawai with a decrease in motivation and their learning achievement, thus forming forms of game rentals such as Gawai, Gagget, Touch Screen Android Mobile, nitendo, sega and others need to get a backup in order to be searched not open when the child is in school hours. Likewise the use of touch screen Android phones by children, but it is part of the development of technology that can not be canceled, but the integration of the use of mobile phones for children must still be monitored and controlled by all parties, requires parents and teachers. Keywords: playing a device; motivation; learning achievement Abstrak Tidak sedikit anak zaman sekarang, yang menyebut dirinya sebagai generasi millennial, ketika ditanya apa cita-citamu, nak? Mereka menjawab bukan lagi ingin jadi dokter, insinyur atau lainnya. Tetapi lebih kepada ingin menjadi seorang youtuber atau gamer. Hasil Penelitian ini menunjukkan adanya keterkaitan antara kecenderungan anak bermain Gawai dengan menurunnya motivasi dan prestasi belajar mereka, maka keberadaan bentuk-bentuk tempat penyewaan permainan game seperti Gawai, Gagget, Handphone Android Touch Screen, nitendo, sega dan lain-lain perlu mendapat masukan agar setidaknya tidak buka pada waktu anak sedang dalam jam pelajaran sekolah . Demikian juga penggunaan HP Android touch sreen oleh anak, meski sudah merupakan bagian dari perkembangan teknologi yang tak bisa dihindari, namun intensitas pemakaian handphone bagi anak tetap harus terus dipantau dan dikontrol oleh semua pihak, terutama orang tua dan gurunya. Kata Kunci: bermain gawai; motivasi;prestasi belajar